Total marrow irradiation-based, reduced-intensity conditioning regimen for elderly patients undergoing hematopoietic cell transplantation for hematological malignancies - Leonardo Javier Arcuri; Mariana Kerbauy; Lucila Kerbauy; Juliana Dall’Agnol da Rocha; Carolina Perrone; Tarcila Datoguia; Jade Zezzi Martins do Nascimento; Morgani Rodrigues; Ana Carolina Pires de Rezende; Eduardo Weltman; Roberto Sakuraba; Andreza Alice Feitosa Ribeiro; et al. (Current Tissue Microenvironment Reports, 2026)
Background Elderly patients are increasingly being offered allogeneic hematopoietic cell transplantation (HCT), and several strategies have been developed to meet their needs. The objective of the current study was to report the feasibility of a reduced-intensity busulfan/fludarabine conditioning regimen with total marrow irradiation in older patients. Methods This single-center study included 28 patients aged 60–77 years with a median follow-up of 34 months. Results Overall survival at 2 years was 46%, relapse rate was 30%, and non-relapse mortality was 23%, yielding a progression-free survival of 46%. Rates of grades II-IV acute GVHD, III-IV acute GVHD, and chronic GVHD were 47%, 8%, and 19%, respectively. Only one patient did not achieve neutrophil engraftment. Three patients experienced sinusoidal obstruction syndrome, and all recovered. Causes of death included disease progression ( n = 10), infection ( n = 5, including one COVID-19 case), and acute myocardial infarction ( n = 1). Conclusion Our results demonstrate the feasibility of an intensified, total marrow irradiation-based conditioning regimen in an elderly cohort, primarily comprising transplants from alternative donors for high-risk diseases. Non-relapse mortality was very low, given the patients’ profile, and compares favorably with others reports reduced-intensity regimen with total body irradiation in older patients. Future studies should compare it to the standard reduced-intensity and non-myeloablative regimens.

Boron and δ11B in hydrological studies: A comprehensive overview based on the IsoBorDat repository - Maddalena Pennisi; Paolo Di Giuseppe; Daniela Andreani; Matteo Salvadori; Lorenzo Gori; Simona Gennaro; Erico Perrone; Roberto Gonfiantini; Antonella Buccianti; Caterina Gozzi (Applied Geochemistry, 2026)

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

LiDAR insights on stand structure and topography in mountain forest wind extreme events: The Vaia case study - Michele Torresani; Leonardo Montagnani; Duccio Rocchini; Vítězslav Moudrý; Andrea Andreoli; Camilla Wellstein; Kenta Koyanagi; Luca Da Ros; Giovanni Bacaro; Michela Perrone; Chiara Salvatori; Irene Menegaldo; et al. (Agricultural and Forest Meteorology, 2024)

Estimation of consistent absolute acceleration and relative displacement floor response spectra in existing masonry-infilled reinforced concrete buildings - Roberto J. Merino; Gianrocco Mucedero; Daniele Perrone; Ricardo Monteiro; Maria Antonietta Aiello; Roberto Nascimbene (Bulletin of Earthquake Engineering, 2024)

Appraisal of seismic design methodologies for suspended non-structural elements in Europe - Roberto J. Merino; Daniele Perrone; Andre Filiatrault (Bulletin of Earthquake Engineering, 2022)

Electrochemotherapy of skin metastases from malignant melanoma: a PRISMA-compliant systematic review - Martina Ferioli; Valentina Lancellotta; Anna Myriam Perrone; Alessandra Arcelli; Andrea Galuppi; Lidia Strigari; Milly Buwenge; Francesca De Terlizzi; Silvia Cammelli; Roberto Iezzi; Pierandrea De Iaco; Luca Tagliaferri; et al. (Clinical & Experimental Metastasis, 2022)
The main treatment of MM metastases are systemic therapies, surgery, limb perfusion, and intralesional talimogene laherparepvec. Electrochemotherapy (ECT) is potentially useful also due to the high response rates recorded in cancers of any histology. No randomized studies comparing ECT with other local therapies have been published on this topic. We analyzed the available evidence on efficacy and toxicity of ECT in this setting. PubMed, Scopus, and Cochrane databases were screened for paper about ECT on MM skin metastases. Data about tumor response, mainly in terms of overall response rate (ORR), toxicity (both for ECT alone and in combination with systemic treatments), local control (LC), and overall survival (OS) were collected. The methodological quality was assessed using a 20-item validated quality appraisal tool for case series. Overall, 18 studies were included in our analysis. In studies reporting “per patient” tumor response the pooled complete response (CR) was 35.7% (95%CI 26.0–46.0%), and the pooled ORR was 80.6% (95%CI 68.7–90.1%). Regarding “per lesion” response, the pooled CR was 53.5% (95%CI 42.1–64.7%) and the pooled ORR was 77.0% (95%CI 56.0–92.6%). One-year LC rate was 80%, and 1-year OS was 67–86.2%. Pain (24.2–92.0%) and erythema (16.6–42.0%) were the most frequent toxicities. Two studies reported 29.2% and 41.6% incidence of necrosis. ECT is effective in terms of tumor response and tolerated in patients with skin metastases from MM, albeit with a wide variability of reported results. Therefore, prospective trials in this setting are warranted.

New insights on the occurrence and conservation status in Italy of Alessioporus ichnusanus (Boletaceae), an IUCN red listed mycorrhizal species - Paola Angelini; Daniele Antonini; Massimo Antonini; Andrea Arcangeli; Pietro Massimiliano Bianco; Giancarlo Bistocchi; Luca Campana; Andrea Ceci; Francesca Floccia; Maria Letizia Gargano; Matteo Gelardi; Giorgio Lalli; et al. (Plant Biosystems, 2021)

Seismic numerical modelling of suspended piping trapeze restraint installations based on component testing - Daniele Perrone; Emanuele Brunesi; Andre Filiatrault; Simone Peloso; Roberto Nascimbene; Clemens Beiter; Roberto Piccinin (Bulletin of Earthquake Engineering, 2020)

Experimental seismic response evaluation of suspended piping restraint installations - Daniele Perrone; Andre Filiatrault; Simone Peloso; Emanuele Brunesi; Clemens Beiter; Roberto Piccinin (Bulletin of Earthquake Engineering, 2020)

Methylation of cytokines gene promoters in IL-1β-treated human intestinal epithelial cells - Fabio Caradonna; Ilenia Cruciata; Ilaria Schifano; Chiara La Rosa; Flores Naselli; Roberto Chiarelli; Anna Perrone; Carla Gentile (Inflammation Research, 2018)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Towards metabolically stable 5-HT7 receptor ligands: a study on 1-arylpiperazine derivatives and related isosters - Enza Lacivita; Paola De Giorgio; Daniela Patarnello; Mauro Niso; Nicola A. Colabufo; Francesco Berardi; Roberto Perrone; Grzegorz Satala; Beata Duszynska; Andrzej J. Bojarski; Marcello Leopoldo (Experimental Brain Research, 2013)

Isolation of a gene encoding for a class III peroxidase in female flower of Corylus avellana L. - Chiara Beltramo; Daniela Torello Marinoni; Irene Perrone; Roberto Botta (Molecular Biology Reports, 2012)

Antiproliferative and cytotoxic effects of some ?2 agonists and ?1 antagonists in tumour cell lines - NicolaAntonio Colabufo; Francesco Berardi; Marialessandra Contino; Mauro Niso; Carmen Abate; Roberto Perrone; Vincenzo Tortorella (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

A new method for evaluating ?2 ligand activity in the isolated guinea-pig bladder - Nicola A. Colabufo; Francesco Berardi; Marialessandra Contino; Roberto Perrone; Vincenzo Tortorella (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)